2000
DOI: 10.1080/08327823.2000.11688430
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric Properties of Wood from 2 to 3 GHz

Abstract: Many applications of microwave energy to wooden materials have been developed in the last few decades, both for treatment and for diagnostic purposes. All these applications require a reliable estimation of the permittivity of the wood species of interest, which is the physical parameter of crucial importance in the absorption of electromagnetic energy. This paper presents results obtained in the dielectric characterization of five wood species in the frequency range from 2 to 3 GHz, including the ISM frequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(23 citation statements)
references
References 6 publications
0
22
0
1
Order By: Relevance
“…The thermal properties of wood in the green state have been determined by the transient plane source technique recently with linear relationship between the thermal properties and moisture content (Dupleix et al 2005). In addition, the dielectric properties of wood are strongly influenced by wood species, density, moisture content, grain direction, temperature, and frequency (Torgovnikov 1993;Olmi et al 2000;Daian et al 2005). There have been only limited studies on the thermal and dielectric properties of wood-based materials.…”
Section: Introductionmentioning
confidence: 99%
“…The thermal properties of wood in the green state have been determined by the transient plane source technique recently with linear relationship between the thermal properties and moisture content (Dupleix et al 2005). In addition, the dielectric properties of wood are strongly influenced by wood species, density, moisture content, grain direction, temperature, and frequency (Torgovnikov 1993;Olmi et al 2000;Daian et al 2005). There have been only limited studies on the thermal and dielectric properties of wood-based materials.…”
Section: Introductionmentioning
confidence: 99%
“…The materials used within the simulation environment include that of two types of wood, a generic fabric, and plastics. Previous studies have shown that the dielectric properties of wood vary greatly with density, and moisture content [17][18][19][20][21][22] . The permittivities of fabrics and plastics have also been shown to vary depending on type and density [23][24][25] .…”
Section: Rcs Characterization Methodologymentioning
confidence: 99%
“…In particular, there was no published data on the microwave dielectric properties of hay. Studies of dielectric properties for other materials such as, peanut hull pellets (Paz et al, 2010a), woody biomass (Olmi et al, 2000;Ramasamy and Moghtaderi, 2010), hardwood (Sahin and Ay, 2004), Aleppo pine, Holm oak and Thuja burl woods (El Alami et al, 2012), softwoods (black spruce, Balsam fir, and Tamarack) (Afzal et al, 2003), oil palm biomass , empty fruit bunch (Omar et al, 2011), and wood and wood-based products (Torgovnikov, 1993) could be found. Based on the available literature and to our knowledge this study is of first kind to reveal the microwave dielectric properties of hay during pyrolysis.…”
Section: Introductionmentioning
confidence: 97%